STABLE VOCABULARY IN LANGUAGE STRUCTURE: COMPONENTS AND ASPECTS - Lenara Selimovna Islyamova (Galaxy International Interdisciplinary Research Journal, 2024)
The article considers phraseological turns as special lexical units reflecting the cultural and historical context. The peculiarity of stable expressions is that they are not formulated by the speaker at the moment of speech, but already exist in a ready-made form in his memory. The sources of stable expressions are folklore, myths, literature, journalism, speech of famous people, memoirs.